2020
DOI: 10.5267/j.msl.2019.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting Jordanian electronic banking services

Abstract: This study aimed to identify the factors influencing on electronic banking services provided by Jordanian banks. Perceived usefulness, ease of use, trust, privacy and security and convenience are the factors investigated in this study. A sample of 300 clients working at King Abdullah University Hospital staff who were active bank accounts in different local banks in Jordan was selected, randomly. To collect the primary data, the study used a questionnaire design based on a 5-point scale. Results of the study f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 26 publications
3
26
0
2
Order By: Relevance
“…Traditional marketing techniques are no longer feasible with the new business environment. Several companies are increasingly examining more effective technologies (Matar et al, 2020;Metcalf et al, 2019;Mogaji, 2019;Adaileh et al, 2019). The term digital marketing stretches and exceeding the use of digital channels to comprehensive technologies for all stages of marketing processes that focus on acquiring and retaining customers.…”
Section: Integrating Artificial Intelligence and Digital Marketingmentioning
confidence: 99%
See 3 more Smart Citations
“…Traditional marketing techniques are no longer feasible with the new business environment. Several companies are increasingly examining more effective technologies (Matar et al, 2020;Metcalf et al, 2019;Mogaji, 2019;Adaileh et al, 2019). The term digital marketing stretches and exceeding the use of digital channels to comprehensive technologies for all stages of marketing processes that focus on acquiring and retaining customers.…”
Section: Integrating Artificial Intelligence and Digital Marketingmentioning
confidence: 99%
“…AI processes information and makes better decisions and eliminating bias in making judgments (Mogaji & Erkan, 2019;Poppleton et al, 2019). The Accumulation of Disparate types of Big data through rapid sensing robots for chatting in social media, e-mail, websites and advertisements in large volumes and at high speed and systematic manner (Rawwash et al, 2020) has increased the power of AI. AI-enabled systems can also identify traits, emotions, or feelings from textual and unstructured data (Poppleton et al, 2019), as well as non-verbal data such as images, and natural language understanding and processing (Mogaji, 2019), for example, customer interaction with brands.…”
Section: Integrating Artificial Intelligence and Digital Marketingmentioning
confidence: 99%
See 2 more Smart Citations
“…Much research by international institutions such as the World Bank and the United Nations Development Program has clearly shown that local governments in developing countries face several challenges of which the most important are financial, administrative and technical ones (Cheema, 1993;Rawwash, 2020;Zenker, Eggers, & Farsky, 2013). Furthermore, a group of scholars agreed that local government units (LGUs) face a range of challenges, perhaps the most important of which are technical competence, financial viability, responsiveness to citizens' needs, public participation, cahttp://dx.doi.org/10.21511/ppm.18 (3).2020.…”
Section: Introductionmentioning
confidence: 99%